2023
DOI: 10.3390/su151612177
|View full text |Cite
|
Sign up to set email alerts
|

Manure Valorization Using Black Soldier Fly Larvae: A Review of Current Systems, Production Characteristics, Utilized Feed Substrates, and Bioconversion and Nitrogen Conversion Efficiencies

Abstract: The growing demand for animal products leads to mounting environmental impacts from the livestock sector. In light of the desired transition from linear to circular nutrient flows and an increasing number of formal commitments toward reducing environmental impacts from livestock production, manure valorization using insects (particularly black soldier fly larvae; BSFL) gains increasing importance. Based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology, this paper i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
0
1
1
Order By: Relevance
“…This may be explained by differences in the decomposition abilities of different BSF larval instar stages, concerning microbiological degradation of pig manure (Choi 2022). The TN values of BSF larvae-treated manure obtained in this study were hardly comparable to those reported in other published studies using chicken, pig, or cattle manure, owing to the different insect larvae or experimental conditions used (Parodi et al 2021;Choi 2022;Grassauer et al 2023). For the TC content and C:N ratio, significant differences between groups were observed for Days 10 and 25 (p < 0.05) but not for Days 0, 5, 15, 20, and 30 (p > 0.05).…”
Section: Decomposition Ability (Experiments 1)contrasting
confidence: 78%
“…This may be explained by differences in the decomposition abilities of different BSF larval instar stages, concerning microbiological degradation of pig manure (Choi 2022). The TN values of BSF larvae-treated manure obtained in this study were hardly comparable to those reported in other published studies using chicken, pig, or cattle manure, owing to the different insect larvae or experimental conditions used (Parodi et al 2021;Choi 2022;Grassauer et al 2023). For the TC content and C:N ratio, significant differences between groups were observed for Days 10 and 25 (p < 0.05) but not for Days 0, 5, 15, 20, and 30 (p > 0.05).…”
Section: Decomposition Ability (Experiments 1)contrasting
confidence: 78%
“… To date, most manure-valorizing BSF larvae production systems operate at the microscale level. However, specific reduction targets for manure-related emissions will likely necessitate large-scale systems at the farm or industrial level [6].  The pilot contributed to technical knowledge development, but more research and longterm support is needed for further uptake by the private sector to make it sustainable.…”
mentioning
confidence: 99%